Prevalence of Angular Cheilitis in the Elderly: A Rapid Review - Clarin, Giofanny; Herawati, Erna; Hidayat, Wahyu (TALENTA, 2023)
The elderly commonly experiences decreased function in various organs, which can impact the immune and digestive systems, as well as increase susceptibility to angular cheilitis (ICD-10 code: K13.0). Furthermore, the high prevalence of malnutrition and the increase in the elderly yearly can affect the incidence of this inflammation. Therefore, this study aimed to evaluate the prevalence of angular cheilitis in the elderly. The rapid review method was employed to accomplish this using the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) guidelines for screening and search procedures. The search was performed through the Google Scholar, PubMed, and ScienceDirect databases using specific keywords and inclusion criteria. A total of 30 observational study articles from 16 countries focusing on several elderly populations were included in this study. The lowest and highest prevalence value was 1% and 46.66%, respectively, with 1,347 out of 14,927 elderly experiencing angular cheilitis. Of the 30 articles reviewed, 23 showed a value below 10%, while the remaining 7 were above 10%. The differences in prevalence could be attributed to the limitations of the articles utilized in this study, which vary widely in terms of sample population characteristics, location, gender allocation, as well as study and data collection methods. This review showed that the prevalence of angular cheilitis in most countries is low. However, the two studies conducted in Indonesia have a high and low prevalence, respectively.